Application of Artificial Intelligence Technologies for the Monitoring of Transactions in AML-Systems Using the Example of the Developed Classification Algorithm - G. Magomedov, S.; S. Dobrotvorsky, A.; M.P. Khrestina, M.; A. Pavelyev, S.; R. Yusubaliev, T. (International Journal of Engineering and Technology, 2018)
The article describes the application of artificial intelligence technologies in Anti Money Laundering (AML) systems for the purpose of transaction monitoring by the example of the developed transaction classification algorithm using machine learning methods. To improve the effectiveness of the algorithm a novel mechanism for forming a unique set of characteristics for the transactions and the participants of financial processes has been developed and a method for constructing a transaction graph has been proposed.Â Â